British Public Opinion Towards the Vietnam War and UK-US Relations During the 1964-70 Labour Governments. Issue 4 (8th July 2021) - Clements, Ben
Abstract: The historiography of the 1964-70 Wilson governments has provided in depth analysis of the Vietnam War within the context of transatlantic relations, while other studies have examined the anti-war movement within British society. But there has been relatively little focus on British public opinion towards the Vietnam War and UK-US relations in the 1960s. To address this gap in scholarship, this article undertakes secondary analysis of opinion poll datasets covering the period 1960-69. It provides new insights into the patterning of public opinion. First, it finds that views supportive of the US war effort and of British government policy were more prevalent amongst men, younger people, and Conservative Party voters. Second, critical appraisals of Wilson as prime minister were not linked with a tendency to hold more negative views of the Vietnam War, either within the general public or Labour voters in particular. Third, a strongly favourable climate of opinion towards broader transatlantic relations deteriorated to some extent in the mid-to-late-1960s, and this shift occurred across societal groups, including supporters of the main parties. Growing opposition to the Vietnam War may have contributed to this shift.